Green event practices: understanding the adaptation of event organisers through a systematic review / Asmahany Ramely ... [et al.] - Ramely, Asmahany; Ab.Talib, Mohd Fadzilillah; Rashid Radha, Jasmine Zea Raziah Radha; Mokhtar, Muhammad Fauzi (Universiti Teknologi MARA, Perak, 2022)
Scholars agreed that the events affect the economy, socio-culture, and the environment across the triple bottom line. However, the impacts across the triple bottom line are not always positive. Hence, the event organisers should implement green practices to reduce the negative impacts of the events. In the meantime, sustainable event management remains unchartered territory in event studies and the effort to systematically review the green event adaptation among event organisers is still lacking. Thus, this study supports further understanding of green event practices by focusing on published literature on green event adaptation among event organisers worldwide. For this purpose, this study conducted a systematic review using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) in four phases. This study applies a qualitative approach to uncover the focused issues related to the adaptation of green event practice. According to the findings of this study, it can be concluded that published literature (journals) as one of the knowledge sources for the event organisers provides inadequate information regarding the green event practices, specifically on the adaptation of green events. Therefore, this study urged further research to include a holistic discussion or exploration of the topic. This effort can provide more information to the event organisers – but not only limited to them –, so that a better understanding regarding green event adaptation in organising their events in the future can be achieved. However, the event organisers are not the only party responsible for the green event practices. Proper action also needs to be taken to prepare the other stakeholders, facilities, resources and local authority to go green.